Wielding an Ambivalent Sword: A Reading of Artemisia Gentileschi’ s Judiths - Gabrielli, Francesca Maria (2009)
The semantic potential of Artemisia Gentileschi’ s treatment of the Judith theme is not confined to the representation of a forceful overturning of the hierarchical opposition between male and female allegedly depicted as heroic. It is the purpose of this paper to show how from a close reading of the four major paintings inspired by the scriptural account - the Judith Slaying Holofernes from the Capodimonte Museum in Naples (1612- 13), the Judith and Her Maidservant from Palazzo Pitti in Florence (c. 1613-14), the Judith Slaying Holofernes in the Uffizi in Florence (c. 1620) and the Judith and Her Maidservant with the Head of Holofernes in the Detroit Institute of Arts (c. 1625) - emerges a number of highly significant details that can be read as subtly problematizing the brutal gender inversion at the center of the story and destabilizing the possibility of interpreting it as an act of female heroism. Thus, instead of empowering the female character, the visual thematization of the man-slaying act tragically reasserts the imprisonment of female and male alike within the patriarchal logic of domination and subjugation. Moreover, the visual field of the paintings (and especially the highly saturated and ambivalent representation of the sword) offers to the viewer the interpretative possibility to transcend the cannibalistic mode of relationality that reproduces the binary dialectic between self and other (cannibalism being one of the patterns of signification implied by the paintings) and allude to a different, non-violent, logic that challenges patriarchy inasmuch as it resists and subverts dualisms.
Projekt MZOS
ENG